Increased Left Atrial Volume and Its Relationship to Vitamin D in Primary Care - Macedo,Erica de Abreu (2019)
Abstract Background: The study is based on the fact that left atrial (LA) volume measurement is a marker of the presence of diastolic dysfunction and that Vitamin D deficiency may be associated with ventricular remodeling, worsening of left ventricular (LV) diastolic and systolic function, and activation of the renin-angiotensin-aldosterone system. Objective: To evaluate whether LAV changes are related to vitamin D deficiency. Method: A cross-sectional, population-based, unicentric study in which 640 patients over 45 years of age enrolled in the Niterói's Médico de Família program, RJ, were evaluated. Patients were submitted to tissue Doppler echocardiography to evaluate the parameters of diastolic and systolic function and vitamin D dosage. The presence or absence of hypovitaminosis D associated with structural and functional cardiac changes was compared between each group. A p < 0.05 value was considered as an indicator of statistical significance. Results: Of the 640 individuals analyzed, hypovitaminosis D was confirmed in 39.2% of the patients, of whom 34.8% had diastolic dysfunction. The most relevant echocardiographic parameters that were statistically significant were non-indexed AEDs and LAV, E'/A' and E wave deceleration time, which were associated with the presence of hypovitaminosis D (P < 0.01). Conclusion: The study of the association of hypovitaminosis D and the appearance of structural and functional cardiac abnormalities may contribute to the discussion of the adoption of one more criterion to select individuals at risk of developing clinical cardiac insufficiency in primary care since, with the use of echocardiography, the subclinical condition of cardiac involvement, with prognostic and treatment implications for the referred patients with hypovitaminosis D, can be identified early.